Marker vaccine potential of foot-and-mouth disease virus with large deletion in the non-structural proteins 3A and 3B. Issue 6 (November 2015) - Biswal, Jitendra K.; Subramaniam, Saravanan; Ranjan, Rajeev; Sharma, Gaurav K.; Misri, Jyoti; Pattnaik, Bramhadev
Abstract: Foot-and-mouth disease (FMD) is a highly contagious, economically important disease of transboundary importance. Regular vaccination with chemically inactivated FMD vaccine is the major means of controlling the disease in endemic countries like India. However, the traditional inactivated vaccines may sometimes contain traces of FMD viral (FMDV) non-structural protein (NSP), therefore, interfering with the NSP-based serological discrimination between infected and vaccinated animals. The availability of marker vaccine for differentiating FMD infected from vaccinated animals (DIVA) would be crucial for the control and subsequent eradication of FMD in India. In this study, we constructed a negative marker FMDV serotype O virus (vaccine strain O IND R2/1975), containing dual deletions of amino acid residues 93–143 and 10–37 in the non-structural proteins 3A and 3B, respectively through reverse genetics approach. The negative marker virus exhibited similar growth kinetics and plaque morphology in cell culture as compared to the wild type virus. In addition, we also developed and evaluated an indirect ELISA (I-ELISA) targeted to the deleted 3AB NSP region (truncated 3AB) which could be used as a companion differential diagnostic assay. The diagnostic sensitivity and specificity of the truncated 3AB I-ELISA were found to be 95.5% and 96%, respectively. The results from this study suggest that the availability negative marker virus and companion diagnostic assay could open a promising new avenue for the application of DIVA compatible marker vaccine for the control of FMD in India. Highlights: DIVA compatible marker vaccine would be crucial for control of FMD in India. A negatively marked FMDV O IND R2/1975 was generated using reverse genetics approach. The marker virus contain dual deletions of AA residues 93–143 and 10–37 in the NSPs 3A and 3B, respectively. The marker virus showed similar growth kinetics and plaque morphology as compared to wild type virus. An indirect ELISA targeted to the deleted 3AB NSP region was also developed as companion diagnostic assay.